Peran Work Life Balance dan Work Compliance dalam Meningkatkan Kinerja Karyawan BSI KCP Bukittinggi Pasar Aur - Windri Oktaviani; Habibatur Ridhah (Lembaga Yasin AlSys, 2026)
Work Life Balance and Work Compliance have received attention in several previous studies, but research that specifically discusses the integration of these two variables in improving employee performance in Islamic banking remains limited. This study aims to analyze the role of Work Life Balance and Work Compliance in improving employee performance at PT Bank Syariah Indonesia KCP Bukittinggi Pasar Aur. This study employed a qualitative approach with a case study design, involving five participants selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed using thematic analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results showed that employees’ Work Life Balance was generally in a fairly balanced condition, although in certain positions imbalance was still found due to work demands and targets that had to be achieved. Work Compliance had also generally been implemented well, although violations by certain employees were still found. Overall, employee performance was in the fairly good category, as reflected in work quality, work quantity, timeliness, commitment, and work initiative. These findings indicate that work-life balance and work compliance play an important role in supporting the improvement of employee performance, while also providing theoretical and practical contributions to the development of human resource management in the Islamic banking sector.